Internal factors supporting business and technological transformation in the context of Industry 4.0 - Lucia Kohnová; Ján Papula; Nikola Salajová (Verslas: Teorija ir praktika / Business: Theory and Practice, 2019)
Radical changes resulting from the Fourth Industrial Revolution strongly affect industrialized European countries. In particular, due to the new technologies that are characteristic of Industry 4.0, it will be essential for companies to make the necessary changes and achieve competitiveness through the implementation of these technologies. In order for companies to be able to make radical changes and innovations, they need to secure all the supporting areas in their organization. This research paper is focused on comparison of companies from Slovakia, Czech Republic, Austria, Germany and Switzerland in the context of readiness for Industry 4.0. This research was part of a research project, while data were collected in the period of 2015-2016. We have analysed companies from selected countries based on 7 areas which are closely interconnected with the business transformation and technology transformation coming from Industry 4.0. The main analysed questions focused on areas such as employee education and training, organizational culture, strategy, or organizational processes, that will be most affected by radical changes in the environment. Research has highlighted the differences between countries as a result of long-standing cultural differences, but at the same time identified the unified influence of the ongoing global debate on the need for technological innovation. With Slovak and Czech companies being below stronger innovators in the maturity of education systems, we strongly advise considering partnering in education which can bring valuable information to businesses that want to take on the wave of innovation.
Keywords: O33; M10; 650; Industry 4.0; business transformation; preparedness; technology; employee education; strategy